PENGAWASAN PEMERINTAH DAERAH DALAM PENYELENGGARAAN ANGKUTAN SEWA KHUSUS DI KABUPATEN BANGGAI - Duru, Christianus; Fality, Firmansyah; Moh. Nur, Nirwan; Hipan, Nasrun (Jurnal Yustisiabel, 2025)
The operation of special rental transportation based on applications in Banggai Regency, the local government is responsible for ensuring compliance with these standards. This study uses an empirical legal method with a study at the Banggai Regency Transportation Agency. Data were obtained through interviews, observations, documentation, and literature studies. The results of the study indicate that supervision is carried out by the Banggai Regency Transportation Agency together with the Banggai Resort Police. This supervision includes fulfilling the requirements for drivers, vehicles, and permits, such as STNK, SIM, Electronic Service Standard Cards, transportation rates, and Minimum Service Standards. However, supervision faces obstacles, especially in regulatory and technical aspects. The lack of synchronization of regulations causes ambiguity in law enforcement. In addition, limited access to the Digital Dashboard is a major obstacle, because this tool plays an important role in distinguishing vehicles operating through applications as special rental transportation